(untitled) (Cadernos de Sociomuseologia, 2025)
: In March 2025, I completed the French translation of Museums and Societal Collapse: The Museum as Lifeboat, the latest book by Canadian museologist Robert R. Janes. Its publication is expected shortly. This work, I did it, so the French-speaking museum community will know how to help their society facing the collapse which, unfortunately, is already knocking on our door. As detailed in the book, this five-phase collapse – financial, then commercial, political, and social, and finally cultural – is foreseeable in the next few decades. Because of the trust societies have in museums, they embody a powerful civic force most capable of cushioning the decline and eventually the collapse of the communities they serve. To do this, they must abdicate their sacrosanct neutrality and professional tribalism, and instead use their socializing skills, making room for discovery, for change, and for excellence in the new narratives they must propose. The world’s approximately 104,000 museums make up the largest franchise of non-profit organizations in the world. If they were to pool some of their resources together and act in a concerted way, the resulting impulse might be fundamental for up-raising social justice, global equality, and planetary well-being. Key Words: collapse; society; sociomuseology; change;